Female Authority during the Knights’ Quest ? Recluses in the Queste del Saint Graal - Anastasija Ropa (Bulletin du Centre d’Études Médiévales d’Auxerre)
Female recluses were prominent in the medieval spiritual landscapes, but, unlike hermits, these vigorously enclosed women are almost non-existent in medieval romance. The thirteenth-century French Lancelot-Grail cycle is no exception, as hermits frequently instruct knights in these texts, but recluses appear only in one of the cycle romances, the Queste del Saint Graal, and even there in two episodes. However, these two episodes are highly important in the dynamic of the quest, with two of the most prominent questers, Perceval and Lancelot, engaging in conversations with the recluses. The recluses are female, yet they instruct knights on matters of chivalric and Christian virtue in an assured, authoritative manner.